First principle calculation of the structural and electronic properties of graphane - Batryshev, D.G.; Yerlanuly, Ye.; Ramazanov, T.S.; Gabdullin, M.T.; Abdykadyrov, B.K.; Amirbekova, G.S.; Daineko, R.A. (Recent Contributions to Physics, 2017)
In this work, a first principle calculation of structural and electronic properties of graphane by density functional theory (DFT) and Hartree-Fock (HF) approximation is considered.On the basis of this hybrid method, quantum-chemical calculations of the minimum energy and bandgap widths of boat-1 and boat-2 types of graphane were carried out. It was found that after optimization of graphane structure (boat-1 and boat-2) the absolute values of the cohesive energy of the atoms exceed the known literary data, which indicates the finding of a more stable structure. After optimization, the structural parameters of graphane boat-2 have been significantly changed, than the boat-1 type, perhaps because the boat-1 type has a more stable structure. Although, the calculations of electronic properties show that the values of the band gap width for both types of graphane were almost unchanged and they still are wide-gap semiconductors that can be used in electronics to create various sensors and transistors.